A citation analysis of faculty publications in Mapùa University with implications on the library collection development - Bautista, Jannice F. (School of Library and Information Studies, University of the Philippines, 2017)
The main purpose of this study was to identify the capabilities of the Mapùa Library in supporting the research needs of its faculty members. The study sought to identify the types of resources utilized, preferred materials, and availability of such in the libraries of the Mapúa Universit